Land issues in Vietnam 2006-14: Markets, property rights, and investment - Thomas Markussen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
This paper uses five waves of the Vietnam Access to Resources Household Survey (VARHS) to analyse land issues in Viet Nam from a number of different angles. The VARHS provides panel data at plot as well as household level and I use this rich data set to present descriptive results on landlessness, land fragmentation, land market activities, and land property rights. I use plot level, fixed effects regressions to investigate the effects of land titles (Land Use Certificates) on household investment. Results show that land titling has a strong and statistically significant effect on household investment in irrigation, although this effect is only present in upland areas.
Keywords: O12; O53; P26; Q15; 330; land; land fragmentation; land markets; property rights; investment; Viet Nam